2003
DOI: 10.1002/jsfa.1393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variety on chemical composition, in situ nutrient disappearance and in vitro gas production of spineless cacti

Abstract: This study determined the chemical composition, in situ ruminal nutrient disappearance and in vitro gas production kinetics of three cactus varieties grown in northeastern Brazil. The varieties were Gigante, IPA-20 and Miúda. Results of the chemical analysis showed no significant differences in ash, ether extract, crude protein (CP) and neutral detergent fibre (NDF) between the cactus varieties. However, acid detergent fibre was highest (P < 0.05) for IPA-20, intermediate (P < 0.05) for Gigante, and lowest (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
54
8
13

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 22 publications
14
54
8
13
Order By: Relevance
“…Most of the values found in this study is in line with those reported in the literature (Batista et al, 2003;Bensadón et al, 2010;DubeuxJunior et al, 2010;Guevara-Figueroa et al, 2010;Silva et al, 2012;Chahdoura et al, 2015).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Most of the values found in this study is in line with those reported in the literature (Batista et al, 2003;Bensadón et al, 2010;DubeuxJunior et al, 2010;Guevara-Figueroa et al, 2010;Silva et al, 2012;Chahdoura et al, 2015).…”
Section: Resultssupporting
confidence: 93%
“…Bensadón et al (2010), studying the nutritional value of cladodes of Opuntia ficus indica, varieties Milpa Alta and Atlixco, found no difference between them in DM, CP, EE, MM, CF and PC. Furthermore, Batista et al (2003), studying the chemical composition of cladodes of two varieties of the genus Opuntia (Giant palm and IPA-20) and one variety of genus Nopalea (Small palm) also reported no difference among them in relation to DM, CP, EE, MM, NFE, P, Mg, Fe, Cu and Zn. However, the researchers reported significant differences among these genotypes for Ca and Mn contents.…”
Section: Resultsmentioning
confidence: 99%
“…The forage cactus contains high levels of pectin (Batista et al, 2003), which contributes to a greater production of acetate. Lower gas production is observed when propionate is formed, due to the absence of CO 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…The spineless cactus occupies a prominent position due to its productivity, nutritional value and distribution in the Brazilian semi-arid. Batista et al (2003) nutrients (TDN) for spineless cacti of the genera Opuntia and Nopalea. Spineless cactus can preserve its nutritional value over a long period; it can be harvested or left in the field for up to four years without impairing its quality and yield.…”
Section: Introductionmentioning
confidence: 99%